THE EFFECT OF INTERNAL CONTROL AND INDIVIDUAL MORALITY ON THE TENDENCY OF ACCOUNTING FRAUD - Santy Setiawan (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
Accounting fraud is a problem commonly faced by both companies and users of financial statements. Accounting fraud often occurs due to weak internal controls. In addition, accounting fraud is also influenced by one’s ethics, especially the morality of individuals to cheat. The purpose of this study is to determine the effect of internal control and individual morality on the tendency to commit accounting fraud. This research is done by using experimental method. The sample used in this research is 85 accounting students of Maranatha Christian University. The testing tool used in this study is a two-way Anova. The results show that internal control has no effect on accounting fraud, but individual morality has an effect on accounting fraud. Individual with low morality will tend to commit accounting frauds rather than those with high morality.